Neurotechnology, AI, and Human Identity: A Christian Anthropological Analysis and Apologetic Response - Susan, Kemigisha (Advances in Social Sciences Research Journal, 2025)
The convergence of neurotechnology and artificial intelligence (AI) is redefining human identity, consciousness, and personhood. As Christian communities grapple with these advancements, a coherent and compelling response is urgently needed. This article develops a robust Christian anthropological framework to understand the implications of neurotechnology and AI on human identity. By integrating insights from theology, philosophy, neuroscience, and AI research, this study addresses the challenges and opportunities presented by these technologies. Through a comprehensive literature review, expert interviews, and case studies, this research constructs a comprehensive apologetic response to equip Christian communities to engage confidently with the emerging landscape of neurotechnology and AI. This study contributes to a nuanced understanding of human identity, informing a Christian response that is both theologically grounded and philosophically informed.